Implementação do tema saúde da mulher para estudantes de nível médio baseada em literatura médico-científica - Morin, Vanessa Lago (2022)
Introduction: Adolescence is a period of transition from childhood to adulthood marked by physical and psychosocial changes, as well as conflicts related to uncertainties and insecurities. And in this sense, the school has a fundamental role in developing educational actions capable of covering this whirlwind of sensations and transformations. For this, it is necessary to approach contents, in a theoretical-practical way, that allow the student to identify problems, raise hypotheses, gather data, reflect on situations, discover and develop solutions committed to the promotion and protection of personal and collective health, and, mainly, apply the acquired knowledge. Objective: To outline a script of contents relevant to the topic of Women's Health, based on medical-scientific literature, which should be included in the teaching of science in high school. Methodology: The contents relevant to women's health were organized into thematic pillars: P1. anatomy of the female reproductive system; P2. histology of the female reproductive system; P3. physiology of the female reproductive system; P4. uterine, tubal, ovarian and breast pathologies; P5. family planning and contraceptive methods; P6. sexually transmitted infections; P7. gestation; P8. labor and delivery; P9. Puerperium and P10. childcare. The development of the sub-themes took place based on the use of active methodologies, specific according to the needs of each theme, after classes, for a group of thirty adolescent girls. A pre-test (PréT) with eleven open questions was applied in the first meeting and a post-test (Post-T) with sixty closed questions in the last meeting, to assess knowledge about women's health before and after the intervention, respectively. As well as, I asked them to build a portfolio during the meetings. Content analysis was used for qualitative data (portfolio); and descriptive analysis for the quantitative data. Results: The post-test revealed better performance in the pillars of family planning, childcare and contraceptive methods; and worse in the physiology of the female reproductive system. Adolescents showed great satisfaction in getting to know their own bodies better, in understanding the physiological changes of each period (menstrual cycle, pregnancy, puerperium, among others), in knowing and knowing how to differentiate the different contraceptive methods and adopting self-care and respect measures. to oneself and to others, according to the following categories of analysis: Approaching university and school; Differentiated methodologies and support material; Relation of contents with everyday life and Self-knowledge. Conclusions: It was observed that it is important to insert women's health content, based on medical-scientific literature, in the high school curriculum as a way of promoting health in the school environment, preventing future damage (health in general; STI; pregnancy unplanned; consequent school dropout, among others) arising from incorrect attitudes due to lack of information and/or dialogue with teachers, family members or health professionals on topics related to women's health. Therefore, the insertion of these contents can promote healthy lifestyle habits, including reproductive health, hygiene, nutrition, self-knowledge and self-care.